The Difference in the Creativity of People Who Are Deaf or Hard of Hearing and Those with Typical Hearing: A Scoping Review - Potměšilová, Petra; Potměšil, Miloň; Klugar, Miloslav (Children (Basel, Switzerland), 2023)
The scoping review aimed to describe differences in creativity between deaf and hard of hearing and typically hearing people. The research question for the review was: what are the differences in the creativity of deaf and hard-of-hearing people in comparison with people with typical hearing? A total of eleven databases were used for the search, as well as sources of the unpublished studies/gray literature. The scoping review was prepared following the Joanna Briggs Institute methodology and PRISMA frame as a basis for reporting scoping reviews. A total of 30 studies were analyzed concerning the selected research areas. Intrinsic creativity was the first area identified. Specific activities for the development of creativity formed the second area for analysis. The third area focused on differences in creativity between deaf and hard of hearing and typically hearing. The fourth area includes studies that call for an equitable research environment.
Keywords: thinking; hard of hearing persons; review; academic; person; creativeness; deaf